The chronology of REITs development in Malaysia / Suhana Mohamed...[et al.] - Mohamed, Suhana; Jaffar, Haliza Hirza; Sham, Rohana; Jambari, Abdul Razak; Zoolkefli, Zuliana; Uteh, Nor Fazlin (Universiti Teknologi MARA, Kedah, 2012)
This research paper investigates the development of Real Estate Investment Trusts (REITs) in Malaysia from 1986 until now. REITs are investment vehicles which enable the flow of funds from investors to the real estate sector of the economy. Their major income comes from rents and most of the profits must be distributed as dividends to their shareholders. The purpose of this research is to document the expansion of REITs market in Malaysia and to provide information to potential investors, especially retail investors, on the current market scenario. As of December 2011, Malaysia has a total of 14 REITs; 11 conventional REITs and 3 Islamic REITs. This is a conceptual paper that will only discuss the development of the Malaysian REITs market over time. The findings revealed that the Malaysian REITs market needs to be more developed. The outcome of this research hopefully will be invaluable to REITs investors and direction on the future direction of the Malaysian REITs market.